Manganese Dioxide–Antimony Trioxide–Lead–Lead Dioxide Vitroceramics Obtained from Recycled Lead Acid Batteries. (22nd September 2022) - Cuibus, D.; Vermesan, H.; Rada, S.; Macavei, S.; Culea, E.
Abstract: The number of spent batteries has increased significantly in recent years due to the use of mobile phones, vehicles, and other high-tech products. In this work, the vitroceramics of the x Sb2 O3 ·5MnO2 ·(95- x )[9Pb·PbO2 ] composition where x  = 0 − 40 mol% Sb2 O3, were synthesized by melt-quenching method using as raw materials the spent plates of a car battery (the anode as the Pb source and the cathode as the PbO2 source), MnO2 and Sb2 O3 powders. The prepared samples were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, and cyclic voltammetry. The electrochemical performance of the antimony–manganese–lead materials used as working electrodes for a car battery were demonstrated by cyclic voltammetry. The combined results from various techniques show that the antimony ions play an important role in the conductive and electrochemical properties.